Assessing beekeeping potential in Oyo State, Nigeria - Ayodeji, B.T.; Dontsop Nguezet, Paul M.; Olalekan, O.S.; Roland, O. (2018)
This paper investigated the technical efficiency and its correlates as well as the profitability status of honey enterprise in Oyo State, Nigeria. A hundred and twenty respondents were sampled using multiple stage sampling techniques and questionnaire was administered to elicit the needed responses. The non-deterministic nature of producing honey informed the use of stochastic production model to assess beekeepers’ technical efficiency while gross margin analysis was adopted to illuminate how profitable honey production is in the area under consideration. The descriptive statistics revealed important socio-economic attributes of beekeepers in relation to beekeeping while the Maximum Likelihood Estimate (MLE) revealed the technical efficiency deciles of beekers within the production possibility frontier. Result revealed that beekeepers are operating close to the frontier of production using the available resources. The elasticity of production was greater than 1, showing an increasing return to scale of production while the budgetary analysis revealed that honey production is profitable. Consequent on the research outcome, beekeeping enterprise has the potential to generate substantial income, generate employment opportunity and meet the nutritional needs of Nigerian populace.